ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), RETURN ON ASSETS (ROA), NON PERFORMING LOAN (NPL), DAN INFLASI TERHADAP LOAN TO DEPOSIT RATIO (LDR): ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), RETURN ON ASSETS (ROA), NON PERFORMING LOAN (NPL), DAN INFLASI TERHADAP LOAN TO DEPOSIT RATIO (LDR) - Agustin, Shinta Dwi; Sjamsuddin, Achmad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This study aims to analyze the management of zakat, waqf and Islamic finance funds managed by Islamic banking. Where is the bank which is a place to collect funds from the community in the form of savings, then channeled back in the form of credit and others to the community. Provision of credit funds to the public can be measured through Loan To Deposit (LDR), where a ratio can indicate the ability of a bank to channel credit funds to third parties. Which can be carried out various tests in channeling bank funds to find out how the influence of CAR, NPL, ROA and inflation on LDR measurements. Then it can be seen from the results of LDR measurements that the form of distribution of CAR and NPL has a significant value to LDR. And then, for the measurement of ROA and inflation, it has no significant value to the LDR. Factors that influence the rise and fall of LDR may be due to the internal and external conditions of banking companies. Internal conditions can be reflected in the bank's financial indicators. The key indicators used in this study are CAR, ROA, NPL.